(untitled) (Bangladesh Pharmaceutical Journal, 2015)
A simple, sensitive and precise reversed phase high performance liquid chromatographic (RP-HPLC) method has been developed for the estimation of naproxen in pharmaceutical dosage forms. The method was developed using the mobile phase comprising of dibasic sodium phosphate buffer (Na2HPO4) at pH 7.80 (adjusted by sodium hydroxide) and acetonitrile in the ratio of 70:30 (v/v) over C-18 column (250 x 4.6 mm, 5?m, Phenomenex Inc.) at ambient temperature. The flow rate was at 0.7 ml/min and the column washing was monitored by UV detector at 225 nm. The retention time of naproxen was 4.8 ± 0.1 min. The recovery was found to be >97% which is demonstrative of accuracy of the protocol. Inter-day and intra-day precision of the newly developed method were less than the maximum allowable limit (RSD% ? 2.0) according to ICH, USP and FDA guidelines. The method showed linear response with correlation coefficient (r2) value of 0.9991. Therefore, the method was found to be accurate, reproducible, sensitive and less time consuming and can be successfully applied for routine analysis of naproxen in pharmaceutical formulations. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22295 Bangladesh Pharmaceutical Journal 16(2): 137-141, 2013